Evaluation of Conditions Concerning the Development of Tourism. Investigation into the Basin of the Parsęta River - Domin, Dominik; Kwiatkowski, Grzegorz; Szymańska, Daniela (Bulletin of Geography. Socio-economic Series, 2009)
The article presents the results of multidimensional evaluation of conditions concerning the development of tourism in rural areas of Parsęta basin. For the purpose the synthetic measure has been applied in reference to 27 variables divided into two groups: suitable for tourism or investing. Having conducted the analysis of the selected variables, the investigated area was divided into three regions: the seaside at the North with very good conditions for the development of the touristic function as its core function, the central region, highly diversified with only moderate touristic capabilities, and finally the southern region, the lake district, with adequate features for the development of tourism.